AKTIVITAS PERCOBAAN MENANAM HIDROPONIK BERBASIS PENDEKATAN HEUTAGOGY BAGI SISWA SEKOLAH DASAR - Ganes Gunansyah; Suprayitno Suprayitno; Maryam Isnaini Damayanti; Heru Subrata (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2023)
Student learning activities carried out online during the Covid-19 pandemic, in addition to providing convenience, also impact the increasingly limited practice of activity-based learning oriented to produce products/works. Overcoming these obstacles, among others, can be facilitated through simple experimental practice activities to plant hydroponic plants to facilitate independent learning, creativity, and collaboration of students with parents. This community service activity was packaged through online training through the Zoom web meeting platform for three sessions, including training material presentation sessions, independent practice of hydroponic planting experiments with the wick system technique, and reflection and follow-up plans. This activity was attended by Elementary School (SD) students and their assistants spread across three Cities/Regencies in East Java, including Surabaya City and Sidoarjo Regency. Participants in this activity are urban communities with limited land, so they are technically suitable for hydroponic planting activities. The experimental practice phase was carried out starting from seeding to nurseries by utilizing training packages in starts and hydroponic planting assistance modules. During the training preparation, implementation and evaluation, participants showed high enthusiasm. Based on the reflection and follow-up of this activity, it is constructive to develop independent learning and collaboration between students and parents. It can be an alternative activity to be applied at home in the surrounding environment and school during the pandemic.